Verticalidade e ausência de diálogo: distorções na comunicação no acesso ao crédito do PRONAF no Arquipélago do Marajó - MENDES, Iran Farias (2020)
The article discusses the distortions in the use of communication by public agencies in access to credit of the National Program for Strengthening Family Agriculture - Pronaf to meet the repressed demand in the Marajó archipelago, a region of the State of Pará that presents low local development. The main aspects of the program, and how the communication between financial institutions, the local populations targeted by the program, and the public bodies involved in rural credit are being questioned. The main objective of this paper is to show the crucial importance of the adequate use of communication as an inclusion mechanism for access to rural credit in the context of family farming in the Marajó archipelago. The research has a bibliographic character and is also based on interviews during a technical visit to public agencies directly related to Pronaf's rural credit policy. It also seeks to evaluate the established forms of interaction of information between organs and the community. The results clearly indicate the difficulties in publicizing and making the program guidelines accessible, because the diversity, peculiarities and complexity of the local reality are not taken into account. To a large extent, the distortions of the model can be attributed to the bureaucracy of the public service, lack of communication between the executing agencies of the policy and, mainly, the lack of communication between them and the local populations.